Wahdatul Ulum) dalam Membentuk Kepemimpinan Berbasis Nilai-Nilai Islam: Studi Kepemimpinan Rasulullah - Nur Haflisma; Fery Dermawan; Muhammad Nawawi; Mohammad Alfarabi; Zaini Dahlan (PT PUSTAKA CENDEKIA GROUP, 2025)
The concept of wahdatul 'ulum (integration of knowledge) is an epistemological approach that attempts to unite religious sciences (ulumuddin) and general sciences in a holistic and integral framework. This study highlights how the principle of wahdatul 'ulum becomes an important foundation in forming leadership based on Islamic values, by emulating the leadership of the Prophet Muhammad SAW as the main model. Through a descriptive qualitative method with a literature study approach, this article finds that integration of knowledge contributes greatly to forming visionary, just, and humanistic leadership. The Prophet not only combined revelation and rationality, but also made morals, knowledge, and strategy as inseparable elements in every policy. This study recommends strengthening the curriculum based on integration of knowledge in Islamic educational institutions in order to be able to produce holistic and transformative leaders.